Utility of Oligonucleotide Array-Based Comparative Genomic Hybridization for Detection of Target Gene Deletions - Wong, Lee-Jun C; Dimmock, David; Geraghty, Michael T; Quan, Richard; Lichter-Konecki, Uta; Wang, Jing; Brundage, Ellen K; Scaglia, Fernando; Chinault, A. Craig (Clinical chemistry (Baltimore, Md.), 2008)
Background: Direct DNA sequencing is the primary clinical technique for identifying mutations in human disease, but sequencing often does not detect intragenic or whole-gene deletions. Oligonucleotide array–based comparative genomic hybridization (CGH) is currently in clinical use to detect major changes in chromosomal copy number. Methods: A custom oligonucleotide-based microarray was constructed to provide high-density coverage of an initial set of 130 nuclear genes involved in the pathogenesis of metabolic and mitochondrial disorders. Standard array CGH procedures were used to test patient DNA samples for regions of copy number change. Sequencing of regions of predicted breakpoints in genomic DNA and PCR analysis were used to confirm oligonucleotide array CGH data. Results: Oligonucleotide array CGH identified intragenic exonic deletions in 2 cases: a heterozygous single-exon deletion of 4.5 kb in the SLC25A13 gene [solute carrier family 25, member 13 (citrin)] in an individual with citrin deficiency and a homozygous 10.5-kb deletion of exons 13–17 in the ABCB11 gene [PFIC2, ATP-binding cassette, sub-family B (MDR/TAP), member 11] in a patient with progressive familial intrahepatic cholestasis. In 2 females with OTC deficiency, we also found 2 large heterozygous deletions of approximately 7.4 Mb and 9 Mb on the short arm of the X chromosome extending from sequences telomeric to the DMD gene [dystrophin (muscular dystrophy, Duchenne and Becker types)] to sequences within or centromeric to the OTC gene (ornithine carbamoyltransferase). Conclusions: These examples illustrate the successful use of custom oligonucleotide arrays to detect either whole-gene deletions or intragenic exonic deletions. This technology may be particularly useful as a complementary diagnostic test in the context of a recessive disease when only one mutant allele is found by sequencing.